Manuscript clarification for ischemic preconditioning improves strength endurance performance - Marocolo, M.; Ide, N. B.; Hohl, R.; da Mota, R. G. (The Journal of Strength and Conditioning Research, 2019)
We have consistently studied ischemic preconditioning (IPC) and exercise performance (7-9). Therefore, we read the article of Carvalho and Barroso (2) carefully. Although the topic is relevant and IPC may be an ergogenic aid, their article may mislead readers to overestimate the IPC effect on the strength endurance performance.